IMPACT OF SODIUM BENTONITE ADDITION TO THE DIETS CONTAINING COTTONSEED MEAL ON PRODUCTIVE TRAITS OF HY-LINE W-36 HENS - A. Gilani; H. Kermanshahi; A. Golian; A. Tahmasbi (Journal of Animal and Plant Sciences, 2013)
This study was conducted to evaluate the effects of cottonseed meal (CSM) treated with sodium bentonite (SB) on the performance of Hy-Line W-36 hens. A 3×3 factorial arrangement with 3 levels of SB (0, 10, and 20 g/kg) and 3 levels of CSM (0, 100, and 200 g/kg) was used with 9 dietary treatments of 4 replicates each. Nine mash diets were fed to 288 commercial Hy-Line W-36 hens from 51-63 weeks of age. Non-significant effect of SB, CSM, or their interaction were noted on egg specific gravity, shell weight percentage, shell thickness, or the percentage of soft-shelled, cracked, or broken eggs. Feeding a diet with a high level of CSM (200 g/kg) resulted in significant (P<0.05) reduction in hen-day egg production, egg weight, and daily egg mass. Hens fed 200 g CSM /kg had the most feed consumption, the worst feed conversion ratio, and the least hen-day egg production and daily egg mass. Hen-day egg production and daily egg mass were improved (P<0.05) in hens fed diet containing 10 g/kg SB. In conclusion, feeding the hens with 10 g SB and 100 g CSM per kg of diet resulted in the best productive characteristics with no detrimental implication.
Keywords: cottonseed meal; Hy-Line W-36 hens; performance; sodium bentonite